2016
DOI: 10.1007/s11701-016-0561-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying force and positional frequency bands in neurosurgical tasks

Abstract: To establish the design requirements for an MR-compatible haptic hand-controller, this paper measures magnitudes and frequency bands of three mechanical motion and interaction components during the performance of neurosurgical tasks on a cadaveric brain. The hand-controller would allow the performance of virtual neurosurgical tasks within the bore of a high field magnet during image acquisition, i.e., functional MRI. The components are the position and the orientation of a surgical tool, and the force interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…The results of this study showed working positional, rotational, and force frequency bands of 3 and 5 Hz. 101 The peak forces of 1:4, 2:9, and 3:0 N were measured using Cartesian coordinate system. The coordinate system originally used to measure the signals is illustrated in Figure 5(c).…”
Section: Technical Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of this study showed working positional, rotational, and force frequency bands of 3 and 5 Hz. 101 The peak forces of 1:4, 2:9, and 3:0 N were measured using Cartesian coordinate system. The coordinate system originally used to measure the signals is illustrated in Figure 5(c).…”
Section: Technical Characteristicsmentioning
confidence: 99%
“…The results showed that major frequency contents of different neurosurgical tasks occurred in the frequency range below 5 Hz. 101 Derivation of kinematic and dynamic equations. Once the workspace and force profiles of the HHC are quantified, the kinematic and dynamic models of the device are governed.…”
Section: Technical Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations